Protecting the Democratic Role of the Press: A Legal Solution to Fake News - Andrea Butler (Washington University Law Review, 2018)
It is difficult to discuss the 2016 presidential election without including the impact of fake news in the conversation, and most commentators deplore the effect of fake news’ proliferation across the internet on American politics and the public. These conversations have centered on the impact fake news had on the presidential election, as well as concerns that the general public is unable to identify fake news. There have even been more immediately dangerous consequences stemming from fake news, such as a gunman showing up to a D.C. pizzeria to liberate children he believed Hillary Clinton was holding hostage there based on a widely-circulated fake news article. Fake news has been shared widely on social media platforms, primarily Facebook, and these platforms’ failure to contain the spread of blatantly false articles has exacerbated these problems. Fake news is a social problem threatening the public’s ability to trust legitimate press outlets and, ultimately, the ability of the press to serve its role in preserving our democracy. Many commentators so far have focused on social solutions to fake news, such as better education for citizens to recognize fake news online, to the exclusion of legal solutions. But the threat fake news poses to the role of a free press in sustaining our democracy necessitates a legal solution to the problem as well. Congress could curb the far-reaching problems of fake news by clarifying the intended implications of § 230 of the Communications Decency Act (CDA) on defamation liability for internet distributors. Applying a modified standard of common law distributor liability specifically targeted to address fake news to internet service providers (ISPs) and websites would hold social media websites like Facebook responsible for fake news that site administrators have been informed is defamatory. This would drastically reduce the oversharing and spreading of fake news. A modified standard of distributor liability would be the best legal solution to the problem of fake news because it merely applies a traditional area of tort law to a new technology. Additionally, it would not create ruinous liability for internet companies because most websites already implement similar monitoring requirements to comply with federal copyright law. This Note will explain the function of the free press in preserving our society, how fake news threatens the press’s legitimacy, and why a legal solution is necessary to protect the press’s democratic role. It will then propose a legal solution to curb the spread of fake news. Part II will explain that there is a consensus among First Amendment theorists that the role of the free press in a democratic society is to inform the public, allowing them to actively participate in elections and the governmental process. It will also explain how fake news undermines the informing function of the press by eroding the legitimacy and credibility of traditional, reliable news outlets, creating an uninformed public unable to participate effectively in our democracy. Part III will explain the history of defamation liability and the development and legal interpretation of the CDA, which eliminated common law distributor defamation liability for ISPs and social media websites. Part IV will outline how the immunization of websites from distributor defamation liability has created a legal environment in which it is impossible for the subjects of fake news to bring defamation lawsuits against distributors to stop the spread of blatantly false and potentially dangerous material about them. It will also explain how amending § 230 of the CDA to reinstate common law distributor defamation liability on a modified basis would be a workable legal solution to the threat fake news poses.
Keywords: press; free press; fake news; 2016 presidential election; pizzagate; Communications Decency Act; CDA; CDA 230; section 230; internet service providers; ISPs; tort law; distributor liability; First Amendment; legitimacy; credibility; reliability; democratic process; defamation; common law defamation